Implementation of chatbots in the government sector: Its impact on taxpayer satisfaction with DGT services - Yanuar, Haadi; Murtanto, Murtanto (WIM Solusi Prima, 2025)
This study aims to evaluate the influence of ease of use, information quality, trust, responsiveness, and data security on taxpayer satisfaction in utilizing the chatbot of the Directorate General of Taxes (DGT). The study population consists of taxpayers who use the DGT chatbot, with a sample selected through a quota sampling method until reaching a quota of 100 respondents. Data collected from these 100 respondents were analyzed using the SEM-PLS model. The analysis results indicate that information quality and data security significantly enhance taxpayer satisfaction. Conversely, trust in the chatbot has a negative but insignificant impact, while ease of use and chatbot responsiveness show positive but insignificant effects on satisfaction. The implications of this research highlight the importance of improving information quality and data security to optimize chatbot services, as well as the need for greater attention to ease of use, trust, and responsiveness to enhance user experience. This study contributes to understanding the factors influencing taxpayer satisfaction and provides practical recommendations for improving chatbot services in the public sector.